A living labs approach for usability testing of ambient assisted living technologies - Dias, M. S.; Vilar, E.; Sousa, F.; Vasconcelos, A.; Pinto, F. M.; Saldanha, N.; Eloy, S. (Design, user experience, and usability: Design discourse. Lecture Notes in Computer Science, 2015)
This paper presents usability tests results with real users during the prototype development phase of two applications for seniors care, AALFred and SmartCompanion. To this aim, usability testing was performed considering a Living Lab approach. Seniors were invited to use the applications in an environment that simulates the one they would use the tested technology during their everyday life. Observation method, thinking aloud and questionnaires were used to collect data related to the systems’ effectiveness and users’ satisfaction, namely their expectations, frustrations and difficulties. Evaluations were performed during the initial phases of product development and results were used to improve the applications, considering the development cycle of User-Centered Design methodology.